Effect of Star Anise (Illicium verum) on the Volatile Compounds of Stewed Chicken. Issue 2 (18th February 2014) - Sun, Lingxia; Chen, Jinping; Li, Miaoyun; Liu, Yanxia; Zhao, Gaiming
Abstract Electronic nose and gas chromatography–mass spectrometry (GC–MS) were used to analyze the effect of star anise on the stewed chicken flavor. Both principal component analysis (PCA) and linear discriminant analysis (LDA) of the electronic nose data suggested that star anise had effect on the stewed chicken flavor. The electronic nose was able to detect a clearer difference in volatile profile of stewed chicken using LDA than using PCA. GC–MS analysis showed that the composition and proportions of volatile compounds were greatly changed, and a spicy flavor was imparted to the stewed chicken with the addition of star anise. Compared with the control group, the peak area and percentage composition of aldehydes increased with the addition of star anise, whereas that of volatile compounds derived from Maillard reaction decreased. Fourteen and 16 key odor compounds were assigned by relative odor activity value (ROAV) in the control group and the star anise group, respectively, including aldehydes, alcohols, esters and sulfur‐containing compounds. The result of cluster analysis showed that ROAV was practicable to assign the key odor compounds of stewed chicken. Practical Applications Pot‐stewed meat products are well‐accepted because of their unique flavors. Spices have significant contributions to the formation of the flavors. Star anise is one of the most widely used spices in traditional Chinese pot‐stewed meat products. However, the effect of spice on meat flavor has not been widely studied, and the mechanism by which spice affects the flavor development is unclear, which limits the modernization of traditional meat products. This study suggested that the addition of star anise just changed the composition and proportions of volatile compounds and imparted a spicy flavor to the stewed chicken. The key odor compounds of meat products have made significant contributions to the overall flavor and determine the overall flavor. In this study, the key odor compounds of stewed chicken were assigned. These results may be helpful for further study of the mechanism whereby spices affect the flavors of traditional Chinese pot‐stewed meat products.